Pengaruh Earning Per Share, Price Earning Ratio Dan Price Book Value Terhadap Harga Saham Pada Perusahaan Manufaktur Subsektor Semen (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The results showed that partially: the Earning Per Share (EPS) variable had a significant positive effect on stock price with value thitung>ttabel (16,821>2,052); the price earning ratio (PER) variable had a significant positive effect on stock price with value thitung>ttabel (2,351>2,052); the price book value (PBV) variable had a significant positive effect on stock price with value thitung>ttabel (3,314>2,052); and The results showed that simultaneous: the Earning Per Share (EPS), price earning ratio (PER) and price book value (PBV) variable had a significant positive effect on stock price with value Fhitung>Ftabel (130,144>2,96).